Comparative DFT Study of Phytochemical Constituents of the Fruits of Cucumis trigonus Roxb. and Cucumis sativus Linn. (12th August 2014) - Gopalakrishnan, Subarayan Bothi; Kalaiarasi, Thangaraj; Subramanian, Ramasamy
Abstract : The hepatoprotective active phytochemical constituents from the ethanolic extracts of the fruits of Cucumis trigonus Roxb. and Cucumis sativus Linn. were identified by GC-MS analysis. The density functional theory (DFT) of these molecules was calculated by density functional B3LYP methods using B3LYP/6-311++G(d, p) basis set. The optimized geometries of phytochemical constituents were evaluated. Physicochemical properties such as HOMO, LUMO, ionization potential, electron affinity, electronegativity, electrochemical potential, hardness, softness, electrophilicity, total energy, and dipole moment have also been recorded. These are very important parameters to understand the chemical reactivity and biological activity of the phytochemical constituents. Glycodeoxycholic acid and 2-(2-methylcyclohexylidene)-hydrazinecarboxamide were found to be effective drugs selected on the basis of their HOMO and LUMO energy gap and softness. The effective properties of these compounds may be due to the presence of amino, carbonyl, and alcohol as a functional group.